Non-binary young people and schools: pedagogical insights from a small-scale interview study. (20th October 2021) - Paechter, Carrie; Toft, Alex; Carlile, Anna
ABSTRACT: While research is increasing into binary trans identities in educational settings, young people identifying as non-binary have been little studied. We explore the school experiences of eight non–binary teenagers aged 13–18. Our findings suggest that both the implicit and explicit curriculum are strongly binary, making it hard for non-binary young people to come out at school. Respondents had needed to educate themselves about gender identity and specifically about the possibility of non-binary identities, with little, if any, support from their schools. As non-binary identities were invisible at school, some did not feel safe there, and they came under pressure from both transphobic bullying and binary expectations of behaviour and self-presentation. Consequently, some respondents feared accessing any available provision for non-binary people, in case it outed them. Institutions should work harder to educate staff about non-binary identities, and non-binary young people should be involved in designing inclusive initiatives.